Dampak Advance Organizer dan Gaya Belajar Terhadap Kemampuan Pemahaman Konsep Matematis - Megananda Elvaliana; Farida; Siska Andriani (Circle: Jurnal Pendidikan Matematika, 2023)
This study aims to determine the impact of the advance organizer learning model and learning style on students’ ability to understand mathematical concepts on the subject matter of Sistem Persamaan Linear Dua Variabel (SPLDV). This study uses a quantitative method with a quasy experiment design type of research. The population in this study were all students of class VIII SMP Negeri 1 Kotagajah, sampling using cluster random sampling technique, then obtained class VIII A as the control class dan VIII B as the experimental class. The result of the study that there is an influence of the advance organizer learning model on the ability to understand mathematical concepts, there is an influence of learning styles on the ability to understand mathematical concepts, and there is no interaction between thw advande organizer learning model and learning styles on the ability to understand mathematical concepts